Valor percebido e o comportamento do consumidor de supermercado: um estudo exploratório em uma média cidade brasileira - Lima Filho, Dario de Oliveira (1999)
This study has been involved with the development of a model for evaluating supermarket value, under the consumer's perspedive. The value concept used in this work originates from the ideathat a behavior should only be carried on if the resulting gain is superior to the pain related to the obtaining of that gain. In Marketing, this means that the consumption of a certain merchandise or service demands a certain amount of sacrifice from the individual (perceived sacrifice) to enjoy the associated benefits (perceived quality). In other words, the consumer needs to take into consideration a series of fadors in a situation of evaluation and choice. For such, in two occasions female supermarket customers of social classes A and B in the City of Campo Grande, Brazil, were consulted, being that one of them was qualitative (n = 25) and another one was quantitative (n = 200). The results indicate that perceived value (PV) is a linear fundion of perceived quality (PQ), but not of perceived sacrifice (PS). Therefore, two of the four hypotheses of the study were not confirmed. About three fourths of the women prefer to go on a main shopping tríp once a month and several smaller ones, in fad this behavior is more evident in the higher age group. For half the interviewees, shopping is more pleasant than work. Most of the women who do not work out like shopping, unlike the women who work out who consider it an obligation. Last, the women who don't work out, the older ones and those who like shopping are the ones who value their supermarket mosto The study also allowed for the verification of the determining charaderistics of the supermarket which the customer takes into consideration. The most valued attributes for the interviewees were replacement of damaged or overdue products and the cleanliness of the store. However, they used exhibition and organization of the products, cleanliness of the store and quality of the produce to perceive value. The results of the hypotheses tests seem to indicate that the use of variables of low perception levei (quality and cost attributes) are not necessary to measuresupermarket PV. The three attributes which remained in the model to explain the PV, through PQ (cleanliness of the store, exhibition and organization of the products and quality of the produce), are moderately (R2 = 24,7%). On the other hand, in the interviewees global evaluation of the stores, QP (now as an independent variable) presentsa coefficient of explanation R2 = 37,4%, a result superior to the one verified when the relationship was given with specific attributes. However, if the customers perceive value only by PQ (global evaluation), the formation of the quality perception is done using specific indicators associated to the product 'supermarket', these indicators includethe three attributes that remained in the model. Thus, a model that includes variables of higher perception (PQ and PS) to infer PV allows us to answer the following question: What is the global evaluation the customers make of their supermarket? On the other hand, a model that judges PV starting from specific attributes (variables of low perception levei) should answerthe following question: How is the customer's perception of value given in relation to his/her supermarket? Other results are discussed and suggestions are also presented for future researches and for the main academic and managerial implications.